2020
DOI: 10.33737/gpps20-tc-103
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on the Pressure Perturbation of a Transonic Aeroelastic Compressor Rig

Abstract: A linear aeroelastic rig was designed to serve as a validation facility for forced response research in axial compressors. This rig focuses on the study of aerodynamic damping at high-reduced frequencies when the central blade oscillates in a controlled manner. The steady and unsteady flow field of the rig has been numerically investigated previously. This paper aims to understand the pressure perturbation throughout the domain, which will give more insight into the actual transonic linear cascade rig and will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Their investigation specifically focused on a transonic cascade and revealed that unsteady pressure reflections on the tailboards play a significant role and must be taken into account during wind tunnel testing. Furthermore, the bottom tailboard was found to cause more pronounced unsteady reflections compared to the upper tailboard [4]. This finding highlights the importance of considering the specific characteristics and effects of each tailboard to accurately analyze fluid flow periodicity in transonic/supersonic cascades [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Their investigation specifically focused on a transonic cascade and revealed that unsteady pressure reflections on the tailboards play a significant role and must be taken into account during wind tunnel testing. Furthermore, the bottom tailboard was found to cause more pronounced unsteady reflections compared to the upper tailboard [4]. This finding highlights the importance of considering the specific characteristics and effects of each tailboard to accurately analyze fluid flow periodicity in transonic/supersonic cascades [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%